Increased global arterial and subcutaneous adipose tissue inflammation in patients with moderate‐to‐severe psoriasis. (1st March 2017) - Hjuler, K.F.; Gormsen, L.C.; Vendelbo, M.H.; Egeberg, A.; Nielsen, J.; Iversen, L.
Summary: Background: Psoriasis is associated with cardiovascular disease; it has been proposed that increased cardiovascular risk is caused by low‐grade systemic inflammation involving organs and tissues other than the skin and joints. Objectives: To investigate signs of vascular inflammation in untreated patients with moderate‐to‐severe psoriasis assessed by 18 F‐fluorodeoxyglucose (FDG) positron emission tomography‐computed tomography. A secondary objective was to assess signs of subcutaneous adipose tissue inflammation. Methods: This was an observational, controlled clinical study including patients with psoriasis ( n = 12, mean ± SD age 61·4 ± 4·1 years, 83% men, mean ± SD Psoriasis Area Severity Index score 14·5 ± 4·3) and matched controls ( n = 23, mean ± SD age 60·4 ± 4·5 years, 87% men). Vascular inflammation was measured using aortic maximal standardized uptake values (SUVmax ) and the target‐to‐background ratio (TBRmax ) of the whole vessel and aortic segments. Subcutaneous adipose tissue inflammation was assessed and compared with regard to SUVmax and TBRmax . Results: Arterial inflammation was increased in patients with psoriasis vs. controls (mean ± SD whole vessel TBRmax 2·46 ± 0·31 vs. 2·09 ± 0·36; P = 0·005). In patients with psoriasis, higher FDG uptake values were observed for all aortic segments except the ascending aorta. Subcutaneous adipose tissue FDG uptake was increased in patients with psoriasis vs. controls (mean ± SD TBRmax 0·49 ± 0·18 vs. 0·31 ± 0·12; P = 0·002). Associations remained significant after adjusting for body mass index and age. Conclusions: Global arterial inflammation and subcutaneous inflammation were significantly increased in patients with moderate‐to‐severe psoriasis compared with controls.